2019
DOI: 10.1002/gch2.201900041
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterial‐Modified Conducting Paper: Fabrication, Properties, and Emerging Biomedical Applications

Abstract: The emerging demand for wearable, lightweight portable devices has led to the development of new materials for flexible electronics using non‐rigid substrates. In this context, nanomaterial‐modified conducting paper (CP) represents a new concept that utilizes paper as a functional part in various devices. Paper has drawn significant interest among the research community because it is ubiquitous, cheap, and environmentally friendly. This review provides information on the basic characteristics of paper and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 132 publications
0
16
0
Order By: Relevance
“…Further, the degree of flexibility of the rGO‐TiO 2 @CP was also checked by repeated folding and unfolding (15 cycles) in both directions (−180° to 180°). It was observed that there was a negligible change in conductivity, which may be due to tearing off of the cellulose thread of paper 42 …”
Section: Resultsmentioning
confidence: 99%
“…Further, the degree of flexibility of the rGO‐TiO 2 @CP was also checked by repeated folding and unfolding (15 cycles) in both directions (−180° to 180°). It was observed that there was a negligible change in conductivity, which may be due to tearing off of the cellulose thread of paper 42 …”
Section: Resultsmentioning
confidence: 99%
“…Notably, these include both the biological specimen and the user. Reviews that deal with long-term exposure of 3D printed materials can also be found as part of biomedical research (139)(140)(141)(142). Given that FDM is the most user-friendly 3D printing technology, it is reasonable to adopt this technology for biological purposes.…”
Section: Current 3d Printing Challenges and Limitationsmentioning
confidence: 99%
“…It can be useful for qualitative and quantitative analyses with a range of analysis. At present, many paper-based sensing platforms have been developed using nanomaterials to enhance the detecting signals [21]. These nanomaterials showed efficient enzyme-like activity [18,22,23].…”
Section: Introductionmentioning
confidence: 99%